Diversity: Its Essential Importance to NCATE Accreditation - Jeff Zacharakis; Joelyn K. Foy (Educational Considerations, 2011)
This issue of Educational Considerations focuses on the National Council for Accreditation of Teacher Education (NCATE) Standard 4 - Diversity. It is not without merit that our teacher preparation institutions are held to a diversity standard by the most prominent accrediting agency.
Keywords: Introduction; diversity; National Council for Accreditation of Teacher Education (NCATE); students; faculty; community; education; Kansas State University